Monitoring intelligibility changes of Kaunas interwar modernism buildings - Zaleckis, Kęstutis; Mlinkauskienė, Aušra; Ivaškevičius, Marius; Povilaitienė, Ingrida (Landscape Architecture and Art, 2025)
The research based on the project “Heritage in Depopulated European Areas” (HerInDep), started in April 2023 and examines the transformation of Interwar (the years between the end of the First World War and the beginning of the Second World War) architecture and its influence on the social and urban development of Kaunas, Lithuania. Kaunas, particularly its central region, holds a significant concentration of Interwar modernist architecture, which has endured substantial urban changes during the Soviet era and pressures from business developments post-1990. In 2023, Kaunas’ modernist architecture was nominated to the UNESCO World Heritage list under “Modernist Kaunas: Architecture of Optimism, 1919-1939,” reflecting its transformation into Lithuania’s provisional capital. Approximately 80% of these heritage properties have distinct characteristics meriting legal protection. The idea of the article is to propose and validate a methodology for assessing the legibility of immovable cultural heritage in an urban environment. Such a methodology could be used not only to understand better the importance of cultural heritage in creating urban landscape identity but also to monitor changes in legibility due to various transformations of the urban fabric, even in the absence of destroyed or otherwise physically affected heritage properties. The paper focuses on the presentation of the space syntax or mathematical graph-based intelligibility model which, because of its simulative natures offers predictive possibilities while pointing out further possibilities of its use for monitoring purposes.